Green turtle hearing identification based on frequency spectral analysis - Yudhana, Anton (Canadian Center of Science and Education, 2010)

(untitled)
It is reported that fishing activities equipped with TED (Turtle Excluder Device) able to reduce the number of turtle by catch. This paper aimed to design a TED using sound technology. In order to dispel a turtle using sound, it is necessary to perform on turtle hearing ability. This study focuses on Green Turtle (Chelonia Midas) species. Three turtles have been measured. They have different age ie: 2, 5, and 9 years. A system known as Auditory Brainstem Responses (ABR) has been used on the green turtle detail analysis. The objective of this paper is to identify green turtle hearing ability by analyzing the ABR spectral. The measurement was taken at Turtle Management Centre Kg. Pantai Panjang Segari Perak Malaysia. The duration measurements were 3 days, December 30, 2008 – January 2, 2009. It was conducted out the turtle tank. From the data obtained can be seen that the 2-year old turtle has a hearing range narrower than 5 years old turtle while 9 years old turtle has the widest frequency range. As for the three types of turtle age, has a maximum power at the same frequency of 300 Hz.